Is Picketing a Crime? - Eaton, Jonathan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This paper focuses on those offenses contained in the Criminal Code that are the most pertinent to picketing: watching and besetting, mischief, public disturbance, unlawful assembly and contempt of court. As well, the role of provincial trespass legislation in regulating picketing is examined. The impact of the Charter of Rights and Freedoms is considered and the overall impact of the criminal law on picketing is assessed.